ChemInform Abstract: Capturing Phase Evolution During Solvothermal Synthesis of Metastable Cu4O3. Issue 29 (29th June 2016) - Jiang, Zhelong; Tian, Shiliang; Lai, Shuqi; McAuliffe, Rebecca D.; Rogers, Steven P.; Shim, Moonsub; Shoemaker, Daniel P.
Abstract: Phase development during the preparation of metastable Cu4 O3 is systematically investigated in the solvothermal reaction of Cu(NO3 )2 in a 1:2 EtOH/DMF mixture (autoclave or evacuated silica tubes, 130 °C, various periods).